Sensitive detection of p53 DNA based on spatially confined fluorescence resonance energy transfer and multivalent assembly of branched DNA. Issue 37 (3rd September 2021) - Liu, Yeling; Sun, Xia; Yuan, Hui; Liu, Bingxin; Zhou, Bingqian; Chen, Xuening; Li, Xia; Xue, Qingwang
Abstract : We present a spatially confined FRET (SC-FRET) probe with a stable structure and strong signal output, consisting of multivalent FRET pairs labeled with FAM or TAMRA. Abstract : A key challenge for the discrete distribution-based Förster resonance energy transfer system (D-FRET) is the reduced intensity and stability of signal probes in complex biological matrices. Here, we present a spatially confined FRET (SC-FRET) probe with a stable structure and strong signal output. It consists of multivalent FRET pairs labeled with FAM or TAMRA. In this assay, p53 DNA was chosen as a model hairpin probe (HP), and two kinds of branched DNA probes (ssDNA-FAM, ssDNA-TAMRA) were involved. Under the action of p53 DNA, the unfolded HP acts as a primer to initiate polymerization extension of KFP polymerase and cleavage of Nb.BbvCI endonuclease, which produces plenty of ssDNA (primer-DNA). The branched DNA is designed to have the same binding core and different sticky ends, the core part of which can self-assemble to form X-shaped branched DNA (X-FAM or X-TAMRA), and the sticky ends of which are complementary to the primer-DNA. Therefore, the primer-DNAs released during the polymerization cleavage process will combine a large number of X-FAM and X-TAMRA in a limited space through complementary base pairing. Fluorescence was transferred from FAM to TAMRA, and a strong FRET response was generated by the locational effects. The proposed SC-FRET system based on the multivalent assembly of branched DNA exhibited a strong FRET response with an LOD of 0.01394 pM. Importantly, it also showed a high-contrast and stable FRET response in HeLa cells. Its superior biological stability is attributed to the large steric hindrance of the compact and rigid frame of the SC-FRET probe, which helps prevent intracellular degradation and provides a powerful tool for biomedical research.